2008
DOI: 10.1213/ane.0b013e31816152da
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Continuous Wound Infiltration with Ropivacaine Versus Single-Injection Paravertebral Block After Modified Radical Mastectomy

Abstract: Continuous wound infiltration of local anesthetics is an effective alternative to paravertebral analgesia after mastectomy with axillary dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 24 publications
1
58
2
Order By: Relevance
“…Sidiropoulou and colleagues in their study on women undergoing modified radical mastectomy with axillary dissection compared preoperative PVB with 20 mL of ropivacaine 0.5% with continuous wound infiltration of ropivacaine 0.5% at a 2 mL/h rate through ON-Q Pain Relief System placed subcutaneously and started at the end of surgery regarding to postoperative pain. They concluded that local anaesthetic infiltration by ON-Q Pain Relief System is comparable to single preoperative injection PVB for postoperative pain [18]. In our study we did not find evidence of a greater effectiveness of ON-Q device compared to PVB in patients who underwent thoracotomy.…”
Section: Citationcontrasting
confidence: 72%
“…Sidiropoulou and colleagues in their study on women undergoing modified radical mastectomy with axillary dissection compared preoperative PVB with 20 mL of ropivacaine 0.5% with continuous wound infiltration of ropivacaine 0.5% at a 2 mL/h rate through ON-Q Pain Relief System placed subcutaneously and started at the end of surgery regarding to postoperative pain. They concluded that local anaesthetic infiltration by ON-Q Pain Relief System is comparable to single preoperative injection PVB for postoperative pain [18]. In our study we did not find evidence of a greater effectiveness of ON-Q device compared to PVB in patients who underwent thoracotomy.…”
Section: Citationcontrasting
confidence: 72%
“…Relatedly, nonsteroidal antiinflammatory agents, gabapentin, and local anesthetic wound infiltration/infusion were not used per the surgeon's preferred standard analgesic regimen, the addition of which may have decreased the differences found between the two treatment groups. [42][43][44] In addition, although the overwhelming number of investigations, including those of the current study, involving breast surgery and paravertebral infusion included the third thoracic level for catheter insertion, [45][46][47][48][49][50][51][52] the optimal level for mastectomy analgesia remains unknown. We did not measure blood levels of nociceptive processing or stress response markers that could have helped elucidate any association of perioperative analgesia with persistent postoperative pain and cancer recurrence.…”
Section: Study Limitationsmentioning
confidence: 91%
“…When compared with direct local anesthetic wound infusion following modified radical mastectomy, singleinjection paravertebral blocks provide superior analgesia and decrease pain-restricted movement during the duration of the ropivacaine 0.5% block [133]. However, following the paravertebral block resolution, these findings were reversed with subjects undergoing local anesthetic infusion directly into their wounds experiencing less pain and pain-restricted movement.…”
Section: Paravertebral Blocks: Compared To Other Analgesic Techniquesmentioning
confidence: 99%